An Analysis of Thermal Comfort at the School Outdoor Spaces: A Case Study of the American School of Creative Science, Dubai, UAE - ABU-QULBAIN, LANA (2022)
Outdoor school spaces are significant spaces which, regardless of a child’s residential area, provide great opportunity for outdoor space exploration leading to overall enhancement to the students’ wellbeing. This paper analyzes the outdoor school spaces of a school in Dubai to optimize its outdoor school spaces and ensure their thermal comfort. To achieve this aim, and using mixed methodology approach of survey, field observation, workshops and ENVI-Met V5.3 software simulation, the initial school outdoor spaces were analyzed and then enhanced by means of several proposed heat mitigation strategies. The enhanced outcome was evaluated against the initial one, using PET (physiological equivalent temperature), revealing that shade separately had the highest impact on its corresponding location with a decrease of up to 16% in PET, but no decrease to the overall PET of the microclimate. Additionally, the addition of vegetation alone had an impact on the microclimate decreasing it by 5%. Thus, combining the strategies of vegetation, shade, green facades/roofs and small water features resulted in 5% to 25% reduction in PET depending on the corresponding location being analyzed. The enhancements also led to reduction in the building energy flux, by up to 5%. The results obtained provide insight and guidelines for school designers and school board members on how to evaluate and enhance the school outdoor spaces to ensure they are thermally comfortable.